Identification of students attitudes towards natural sciences at Adhyaksa 1 Junior High School, Jambi City - Tanti Tanti; Dwi Agus Kurniawan; Boby Syefrinando; Mahbub Daryanto; Rini Siski Fitriani (Intelektual Pustaka Media Utama, 2021)
The study examined the attitudes of students at Adhyaksa 1 Junior High School in Jambi, Indonesia towards science subjects. This type of research is a mixed method. This study involved 136 students of Adhyaksa 1 Junior High School in Jambi City. The instruments used consisted of questionnaires and interviews. The questionnaire used was adapted from the study astalini and kurniawan with a Cronbach alpha value of 0.842 with a valid number of claims of 56. Data were analyzed using descriptive statistics processed using the SPSS program. The results of the seven indicators are the social implications of science, normality of scientists, attitudes towards science inquiry, adoption of scientific attitudes, pleasure in learning science, interest in learning more science, career interest in science, this dominant in the moderate category, which means students are sufficient in learning science. With this research, it is expected to be able to measure students 'attitudes towards how students' attitudes towards the natural science course in Adhyaksa 1 Junior High School, Jambi City.